(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
This study explores the use of presuppositions in the dialogues of the main characters, Sophie and Agatha, in The School for Good and Evil movie. Presupposition, as an essential element in communication, allows speakers to express implied meanings that are not directly stated. In cinematic discourse, it plays a significant role in shaping character interactions and maintaining narrative coherence. The research aims to identify the types of presuppositions used and analyze their meanings, focusing on how these implicit assumptions influence character development and audience understanding. The study adopts Yule’s (1996) theory of presupposition and Leech’s (1981) theory of meaning, applying a qualitative descriptive method. Data were collected through documentation and note-taking techniques, then analyzed by identifying instances of presupposition within the dialogues. Each example was categorized based on Yule’s six types: existential, factive, lexical, structural, non-factive, and counterfactual. The analysis also considered the contextual meaning and pragmatic implications of each type. The findings reveal that existential and structural presuppositions appear most frequently, underlining the importance of shared background knowledge in character exchanges. Overall, the study highlights how presuppositions enrich storytelling by conveying hidden meanings, thus contributing to the broader understanding of pragmatics in movie dialogue analysis.